Modeling the economic performance of small ruminant pastoralist flocks and financial impact of changes in reproductive performance and mortalities in Kajiado county, Kenya - Arnold, Jean-Christophe; Onono, Joshua; Ballesteros, Cristina; Aboge, Gabriel; Alarcon, Pablo (Frontiers in Sustainable Food Systems, 2024)
This study investigated the economic performance of pastoralist small ruminant flocks in Kajiado county, Kenya, and the financial impact of mortalities and changes in performance indicators. A survey of 129 pastoralist small ruminant flocks captured production and economic data for a 12-month period via interview. Simulation models were then developed for flocks with different performance levels and trading activities. Their gross margins, and the financial impact from mortalities, were estimated. Sensitivity analyses were conducted for select performance indicators to assess their relative economic importance. On average, pastoralists who were not purchasing supplementary feed (79% of flocks) had gross margins of KSh 3,016 – KSh 3,123 per reproductive female. Goat production generated 2.43-2.51 times greater returns than sheep production. High efficiency mixed flocks achieved 2.04-2.06 times greater returns than medium efficiency flocks, and 12.19-14.25 times greater returns than low efficiency flocks. Pastoralist-only flocks had 3.82-4.01 times greater returns than pastoralist-traders. Financial losses due to mortality were on average 17.81% of the starting flock value. Fecundity and abortion rates in sheep, and parturition rate in goats, had the greatest economic impact. The developed models could support decision-making towards improving the economic performance of pastoralist flocks and the evaluation of interventions and external shocks.